A novel key driver gene of Alzheimer's disease impacts AD‐related cognitive deficit, pathology and neuro‐inflammation in sex‐ and APOE‐specific manners. (1st February 2022) - Cai, Dongming; Guo, Lei; Cao, Jiqing; Zhang, Larry; Huang, Min; Hou, Jianwei; Zhu, Li; TCW, Julia; Zhong, Minghao; Goate, Alison M.; Zhang, Bin
Abstract: Background: Alzheimer's Disease (AD) has complex etiologies and the impact of sex on AD varies over the course of disease development. Literature provides some evidence of sex‐specific contributions to AD. However, molecular mechanisms of sex biased differences in AD remain elusive. Multi‐omics data in tandem with systems biology approaches offer a new avenue to not only dissect sex‐stratified molecular mechanisms of AD but also develop sex‐specific diagnostic and therapeutic strategies for AD. Method: We integrated RNA expression datasets from the para‐hippocampal gyrus of the Mount Sinai Medical Center Brain Bank (MSBB) and the prefrontal cortex from the Religious Orders Study and Rush Memory and Aging Project (ROSMAP) to perform multiscale network analysis. The differentially expressed genes (DEGs) between AD and control, female and male, ApoE3 and ApoE4 genotype were rank‐ordered based on their relevance to clinical dementia rating scale (CDR) and AD pathology (Braak stage, CERAD and plaque density). The trend analyses and gene co‐expression network analysis were then performed to identify key drivers with sexually dimorphic expression patterns or differentially respond to APOE genotypes between sexes. Result: In this study, we identified ldl receptor‐related protein ( lrp10 ), a receptor possibly involved in the uptake of ApoE and APP trafficking as the highest‐ranked key driver gene candidate accounting for the sex differences in AD. Lrp10 mRNA was increased in female AD patients when compared to female controls or male AD patients. In contrast, LRP10 protein levels were reduced in AD when compared to controls, suggesting possible post‐translational modifications of LRP10 in AD human brains. Gene perturbation studies in EFAD mouse hippocampal brain regions suggest that over‐expression of lrp10 improved cognitive function, reduced Aβ42 and p‐Tau, and increased microglial recruitment around amyloid plaques in female E4FAD mice. In contrast, down‐regulation of lrp10 exacerbated cognitive impairment as well as increased brain Aβ42 and total tau levels in male E3FAD mice. Conclusion: These results strongly support our hypothesis that lrp10 is a causal regulator gene for AD, whose expression is strongly associated with cognition performance in sex‐ and APOE ‐specific manners. Our findings further implicate a role of lrp10 in regulating microglial function and neuro‐inflammation in AD.